Design, construction and validation of a planar probe for measuring complex relative permittivity of materials - Piladaeng, Nawarat; Angkawisittpan, Niwat; Nuan-On, Adisorn (International Journal of Engineering and Technology, 2019)
A planar probe for inspecting the complex relative permittivity of materials was redesigned and constructed in this research. The Â Â Â Â Â Â proposed planar probe was made of the Arlon AD260A PCB with the coaxial and microstrip structure. Experiments were conducted in the frequency range of 0.5-6 GHz. Ethanol and methanol were used as samples to validate the probe. It was found that the complex Â Â relative permittivity of the samples had a good tendency to the references in the frequency range of 0.5-2 GHz. Moreover, this redesigned probe provided improved accuracy on the measurement compared to the conventional planar probe.